2004
DOI: 10.1143/jjap.43.6769
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Characteristics of Polymer Film Oriented under a Strong Magnetic Field

Abstract: The possibility has been indicated that polymers with helical chirality, such as poly-γ-benzyl-L-glutamate (PBLG) and poly-L-lactic acid (PLLA), exhibit a large shear piezoelectric constant. To attempt the realization of a PBLG membrane with a large piezoelectric constant, we fabricated the PBLG membrane oriented by magnetic field force. Concretely, the PBLG membranes were casted from 1,2-dichloroethane solution with various PBLG concentrations under the magnetic field generation equipment incorporating a supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…Although relatively small, this value is close to the results from Fukada's original work [14]. This result makes us question Nakiri and Fukada's recently reported high d 14 value of 26 pC/N, which they claim to be due to enhanced alignment of PBLG helices by poling under extremely high magnetic field (10 Tesla) [20]. This value needs to be validated as it seems unexpectedly high, especially when compared to our PBLG film, which also has very high orientational order due to the unique electrospinning and hot pressing process.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Although relatively small, this value is close to the results from Fukada's original work [14]. This result makes us question Nakiri and Fukada's recently reported high d 14 value of 26 pC/N, which they claim to be due to enhanced alignment of PBLG helices by poling under extremely high magnetic field (10 Tesla) [20]. This value needs to be validated as it seems unexpectedly high, especially when compared to our PBLG film, which also has very high orientational order due to the unique electrospinning and hot pressing process.…”
Section: Resultssupporting
confidence: 87%
“…When films of helical polymers are exposed to shear stress by application of tensile forces 45 • to the helical axis, the shear deformation of the helical chains follows the chiral nature of the polymer chains, which results in the development of new net electrical dipole across the film thickness direction [23]. Recently in 2004, Nakiri and Fukada reported that the piezoelectric coefficient d 14 of this film can be as high as 26 pC/N if polymers are aligned by strong magnetic field (10 Tesla) [20]. In Fukada's work, the alignment of the PBLG molecules is mainly caused by the interactions between the external magnetic field and the induced magnetic field originating from the electron-rich benzyl side chains.…”
Section: Classification Of Piezoelectric Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Tajitsu et al [54] undertook to apply a strong magnetic field to orient the helical molecules of PBLG during cast from the 1,2-dichloroethane liquid crystalline solution. X-ray diffraction patterns clearly showed the helical molecules are oriented perpendicularly to the magnetic field (Fig.23).…”
Section: Biopolymersmentioning
confidence: 99%
“…4,5,8) We have reported that the orientation technique using a strong magnetic field was effective for PBLG, and the shear piezoelectricity was also improved. 22,23) However, at present, it is not possible to obtain a uniform PBLG film with high shear piezoelectricity, and the mechanism of the induction of the shear piezoelectricity of a PBLG film oriented by a strong magnetic field has not been sufficiently clarified. Also, in previous reports, 23,24) it is indicated that a domain with a diameter of about 100 nm is required if a magnetic field of 10 T is applied to a sample with a magnetic susceptibility of 10 À7 at a temperature of 340 K. [16][17][18][19][20][21] In this study, the shear piezoelectricity of a PBLG film oriented by a strong magnetic field was investigated in order to obtain optimal conditions for fabricating a stable film with a high shear piezoelectric constant.…”
Section: Introductionmentioning
confidence: 99%